Inhibition of NOX1/4 with GKT137831: a potential novel treatment to attenuate neuroglial cell inflammation in the retina - Deliyanti, Devy (J Neuroinflammation, 2015)
BACKGROUND: Inflammation and the excess production of reactive oxygen species (ROS) contribute significantly to the pathogenesis of ischemic retinopathies such as diabetic retinopathy and retinopathy of prematurity. We hypothesized that GKT137831, a dual inhibitor of NADPH oxidases (NOX) 1 and NOX4, reduces inflammation in the ischemic retina by dampening the pro-inflammatory phenotype of retinal immune cells as well as macroglial Müller cells and neurons. METHODS: Ischemic retinopathy was induced in Sprague-Dawley rats by exposure to 80 % O(2) cycled with 21 % O(2) for 3 h per day from postnatal day (P) 0 to P11, followed by room air (P12 to P18). GKT137831 was administered P12 to P18 (60 mg/kg, subcutaneous) and comparisons were to room air controls. Retinal inflammation was examined by measuring leukocyte adherence to the retinal vasculature, ionized calcium-binding adaptor protein-1-positive microglia/macrophages, and the mRNA and protein levels of key inflammatory factors involved in retinal disease. Damage to Müller cells was evaluated by quantitating glial fibrillary acidic protein-positive cells and vascular leakage with an albumin ELISA. To verify the anti-inflammatory actions of GKT137831 on glia and neurons involved in ischemic retinopathy, primary cultures of rat retinal microglia, Müller cells, and ganglion cells were exposed to the in vitro counterpart of ischemia, hypoxia (0.5 %), and treated with GKT137831 for up to 72 h. ROS levels were evaluated with dihydroethidium and the protein and gene expression of inflammatory factors with quantitative PCR, ELISA, and a protein cytokine array. RESULTS: In the ischemic retina, GKT137831 reduced the increased leukocyte adherence to the vasculature, the pro-inflammatory phenotype of microglia and macroglia, the increased gene and protein expression of vascular endothelial growth factor, monocyte chemoattractant protein-1, and leukocyte adhesion molecules as well as vascular leakage. In all cultured cell types, GKT137831 reduced the hypoxia-induced increase in ROS levels and protein expression of various inflammatory mediators. CONCLUSIONS: NOX1/4 enzyme inhibition with GKT137831 has potent anti-inflammatory effects in the retina, indicating its potential as a treatment for a variety of vision-threatening retinopathies.